Measuring changes in the plantar temperature distribution in diabetic patients - Hernandez-Contreras,D; Peregrina-Barreto,H; Rangel-Magdaleno,J; Orihuela-Espina,F; Ramirez-Cortes,J (IEEE, 2017)
Temperature distribution in the sole is an indicator of peripheral vascular abnormalities associated with the diabetic foot. This paper presents a criterion to identify changes in the plantar temperature distribution that can be related to diabetic foot complications. This criterion, based on Kullback-Leibler and Jensen-Shannon divergences, allows identification of changes in the plantar temperature distribution by comparing the samples with a reference distribution from healthy subjects. A 82% of 200 samples of diabetic patients presented a significant change in the temperature distribution which can be a precursor of any complication. These results suggest that with this method, it is possible to detect changes in the plantar temperature distribution. Potentially, this method can be exploited for medical diagnostic support.